Peter, Paul, and Mary Magdalene : the followers of Jesus in history and legend - Ehrman, Bart D. (Oxford University Press, 2006)
From the Publisher: Bart Ehrman, author of the bestsellers Misquoting Jesus and Truth and Fiction in The Da Vinci Code, here takes readers on another engaging tour of the early Christian church, illuminating the lives of three of Jesus' most intriguing followers: Simon Peter, Paul of Tarsus, and Mary Magdalene.